TILLAGE AND NITROGEN MANAGEMENT EFFECT ON ENERGY EFFICIENCY IN AEROBIC RICE - G , NAVEEN KUMAR; B , SREEDEVI; V, CHANDRIKA (The Journal of Research ANGRAU, 2026)
A field experiment conducted at the Indian Institute of Rice Research, Hyderabad, Telangana,India, during the rabi season (November-April) of 2022 and 2023 assessed the impact of tillagepractices and nitrogen fertilizer schedules on energy efficiency in aerobic rice. The study employedthree tillage treatments (T) and five nitrogen fertilizer schedules (N) in a strip plot design with threereplications. Results revealed that Conventional tillage (T1) showed higher energy input, whereaszero tillage (T3) showed lower energy input. Higher Gross Energy Output (GEO), Net Energy Output(NEO), Energy Use Efficiency (EUE) and Energy Productivity (EP) obtained under Conventionaltillage (T1) which is statistically comparable with minimum tillage with residue retention (T2) andsignificantly higher over zero tillage (T3). Zero tillage (T3) resulted in the highest energy intensity inphysical terms (EIP). Energy Intensity in Economic terms (EIE) was not significantly influenced bytillage practices. Among nitrogen fertilizer schedules, the treatment 100% RDN + foliar spray of2.5 ml l-1 nano urea at tillering and before panicle initiation stage (N2) yielded the highest energymetrics, including GEO and NEO, EUE, EP and EIP which is statistically comparable to 100%RDN (N1). Conventional tillage (T1) and 100% RDN (N1) treatment demonstrated superiorperformance across various energetics, emphasizing their effectiveness in enhancing the energeticefficiency of aerobic rice cultivation. Overall, conventional tillage and recommended nitrogenmanagement were most effective, while conservation tillage performed on par with conventionaltillage in aerobic rice.